Antecedents of proactive customer service performance in hospitality: a meta-analysis - Yan, Zhen; Mansor, Zuraina; Choo, Wei Chong (Informa UK, 2023)
As an emerging construct, proactive customer service performance (PCSP) has been largely explored in recent years. However, previous research focusing on PCSP has been fragmented, each investigating the associations between a single or few selected antecedents and PCSP in the hospitality industry. The present study aims to meta-analytically examine the direction and magnitude of effect sizes of the relationships between PCSP and its main antecedents as well as the moderating effect of national culture in the hospitality context. A quantitative meta-analysis was conducted to test the hypotheses based on 17 antecedents and 42 independent studies (N=13,333). The antecedents of PCSP can be categorized into job attitudes, job strain, leader behaviors, performance, family context factor, workplace factors, positive psychological states, emotional labor and individual determinants. The results demonstrated that empowering leadership had the strongest impact on PCSP, followed by mindfulness and thriving at work. The results also indicated that national culture was a key moderator in the analysis. To the authors knowledge, this is the first meta-analysis to collect, synthesize and analyze the theoretical links between PCSP and its antecedents and moderator has also been verified. Whats more, this study has discussed future research directions for PCSP in hospitality.